2015
DOI: 10.1109/tla.2015.7273782
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring and control of the processes involved in the capture and filtering of biogas using FPGA embedded fuzzy logic

Abstract: This article focuses on the development of an intelligent control platform capable of improving the capture and filtration of biogas with the aim of raising the calorific value of the fuel. The biogas was produced in an upflow anaerobic sludge blanket (UASB) reactor at the sewage treatment plant (STP) located near to the town of Los Angeles, Campo Grande, Mato Grosso do Sul, Brazil. For the purposes of system identification, the concentrations, flow rates and pressures of the gases were continuously monitored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 15 publications
0
3
0
1
Order By: Relevance
“…Highlighted also, in agreement with Vanti et al (2015), is that raw biogas has a strong odor, low heat potential and is highly corrosive, which means that it is not indicated for internal combustion engines, thus there arises the need for purification processes to be applied to the raw product in order to elevate its heat potential and remove components that are responsible for corrosion and the bad odor.…”
Section: Author(s) Agree That This Article Remain Permanently Open Acmentioning
confidence: 68%
“…Highlighted also, in agreement with Vanti et al (2015), is that raw biogas has a strong odor, low heat potential and is highly corrosive, which means that it is not indicated for internal combustion engines, thus there arises the need for purification processes to be applied to the raw product in order to elevate its heat potential and remove components that are responsible for corrosion and the bad odor.…”
Section: Author(s) Agree That This Article Remain Permanently Open Acmentioning
confidence: 68%
“…There have also been machine learning applications in the natural sciences, that also enable intelligent decision-making systems, and artificial and computational intelligence in the world of data science. Daily time series data in a wastewater treatment plant were used as input for developing a support vector machine model by Manu and Thalla (2017), and it was observed that is possible to define the relation between dependent and independent variables with help of machine learning algorithms [135,136].…”
Section: Process Optimization Through Implementation Of Artificial In...mentioning
confidence: 99%
“…Major contributions by ML approaches have increased the speed of process data analysis while reducing the number of experiments required and the number of independent variables to be monitored, eventually allowing for the identification of optimal process conditions. In this context, machine learning methods have been investigated for process optimization in biogas productions [7,8] and wastewater treatments [9,10]. Only more recently have a few attempts at modeling fermentation processes with machine learning been explored [11,12].…”
Section: Introductionmentioning
confidence: 99%